2011
DOI: 10.1016/j.ibmb.2011.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis: A story of a successful bioinsecticide

Abstract: Bacillus thuringiensis (Bt) bacteria are insect pathogens that rely on insecticidal pore forming proteins known as Cry and Cyt toxins to kill their insect larval hosts. At least four different non-structurally related families of proteins form the Cry toxin group of toxins. The expression of certain Cry toxins in transgenic crops has contributed to an efficient control of insect pests resulting in a significant reduction in chemical insecticide use. The mode of action of the three domain Cry toxin family invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
612
1
44

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 912 publications
(662 citation statements)
references
References 93 publications
5
612
1
44
Order By: Relevance
“…Recent, research has classified B. thuringiensis as a bacterial pathogen of alternative nematode hosts (2)(3)(4), which may help to explain the complex ecology of B. thuringiensis that was previously thought to have a sole insect host (2,5,6). This finding further contextualizes already established interactions between B. thuringiensis and nematodes (1)(2)(3)(4)7), including free-living and parasitic species.…”
mentioning
confidence: 80%
“…Recent, research has classified B. thuringiensis as a bacterial pathogen of alternative nematode hosts (2)(3)(4), which may help to explain the complex ecology of B. thuringiensis that was previously thought to have a sole insect host (2,5,6). This finding further contextualizes already established interactions between B. thuringiensis and nematodes (1)(2)(3)(4)7), including free-living and parasitic species.…”
mentioning
confidence: 80%
“…Therefore, it is widely used as a biopesticide for agricultural and public health applications. More recently, some ICP genes have been successfully expressed in transgenic plants, leading to a higher yield and the lowered use of chemical pesticides (6).…”
mentioning
confidence: 99%
“…The formation of lytic pores causes the uncontrolled release of ions, the collapse of the epithelia that stops the larvae from feeding and finally leads to the death of the larvae. Bravo et al, 2011 In line with this gap, we have reported the successful development of transgenic pea lines expressing cry1Ac gene from Bacillus thuringiensis. Negawo et al, 2013 The cry1Ac gene Cheng, Sardana, Kaplan, Altosaar 1998;Sardana 1996 is one of the commonly used Bt cry genes to develop transgenic lines in many plant species such as tobacco, cotton, maize, soybean, tomato and rice, Cheng, Sardana, Kaplan, Altosaar 1998;Perlak 1990;Bohorova 1999;Stewart Jr CN 1996;Mandaokar et al, 2000 to become resistant to Lepidopteran pests.…”
Section: Introductionmentioning
confidence: 99%